PENGARUH KOMPETISI ALANG-ALANG (Imperata cylindrica L.) DENGAN PUPUK K TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Phaseolus radiatus L.) - Yernelis Syawal (Jurnal Agroekoteknologi, 2011)
The research aimed to know the influence of competition with weeds K fertilizer on the growth and yield of green bean plant, has been held in the shadow home Crop Science Study Program Graduate of Sriwijaya University, from September to December 2010. The designs used in this study were factorial randomized block design with three replications. The first factor is rhizome reeds: R1 = 0, R2 = 2, R3 = 4, R4 = 6, R5 = 8 rhizome polybag-1. Factor II doses of fertilizer K, K1 and K2 = 0 g = 1.25 g KCl polybag-1. The results showed that the growth and yield of green beans decreased with the increasing number rhizome weeds that compete, either with or without fertilizer K fertilizer K. But with the growth and yield of K fertilization gives better results than without fertilizer K.Key words: competition, weed, fertilizer K, green beans